Structure-property relationship in charge transporting behaviour of room temperature liquid crystalline perylenebisimides - Prajitha, K. P.; Chithiravel, Sundaresan; Krishnamoorthy, K.; Asha, S. K. (Journal of Materials Chemistry C, 2014)
A homologous series of pentadecyl phenol functionalized perylenebisimide (PBI) terminated with trialkoxy gallate esters was synthesized, where the terminal alkyl chain length was varied from n = 4 to 12 (PBI-En). The thermotropic liquid crystalline (LC) characteristics of the molecules were analyzed using differential scanning calorimetry (DSC), polarized light microscopy (PLM) combined with variable temperature wide angle X-ray diffraction (WXRD) techniques. A clear odd-even oscillation was observed in the melting as well as isotropization enthalpies as a function of alkyl spacer length in the terminal gallate unit, with the even spacers exhibiting higher values. The higher members of the series with n > 8 exhibited thermotropic liquid crystalline textures in the PLM, which remained stable until room temperature. The nature of the LC phase was identified to be columnar rectangular and columnar hexagonal based on detailed analysis of the WXRD pattern recorded in the LC phase. The WXRD pattern of the room temperature LC frozen samples indicated a nearly constant intra columnar stack distance of similar to 3.7 angstrom for all the members. The space-charge-limited current (SCLC) values of the LC frozen sample films were analyzed for dependence of the bulk mobility estimate on the nature of the LC phase. The columnar hexagonal phase exhibited a mobility value one order (10(-3) cm(2) V-1 s(-1)) higher than that of crystalline (10(-4) cm(2) V-1 s(-1)) and two orders higher than that of columnar rectangular phase (10(-5) cm(2) V-1 s(-1)), indicating a strong dependence of packing on bulk mobility.

Detailed study on the thermal, photo-physical and electrochemical properties and OFET applications of D-pi-A-pi-D structured unsymmetrical diketopyrrolopyrrole materials - Bharath, D.; Chithiravel, Sundaresan; Sasikumar, M.; Chereddy, Narendra Reddy; Shanigaram, Balaiah; Bhanuprakash, K.; Krishnamoorthy, K.; Rao, V. Jayathirtha (RSC Advances, 2015)
A series of seven unsymmetrical diketopyrrolopyrrole (DPP) derivatives with donor-pi-acceptor-pi-donor (D-pi-A-pi-D) architecture have been designed, synthesized and well characterised. The effect of the electron donating capacity and extent of electronic conjugation of the end-capping units on the thermal, photo-physical and electrochemical properties of the synthesized materials was thoroughly investigated using various experimental techniques and theoretical calculations. Organic field-effect transistors (OFETs) were fabricated using these materials to obtain their hole/electron transporting characteristics. All these materials showed moderate to good hole transporting ability, and the OFET fabricated using the DPP-derivative with benzofuran and pyrene end groups exhibited a hole mobility of 6.7 x 10(-4) cm(2) V-1 s(-1) with VT of similar to 9 V. The observed photo-physical, electrochemical, thermal, and charge carrier properties of the synthesized DPP-derivatives indicated their applicability in various areas like organic photovoltaics, disposable electronics and biomedical devices.

Themed issue on ``Organic field-effect transistors: interfacial phenomena and electronic properties'' - Krishnamoorthy, K.; Facchetti, Antonio F.; Hu, Wenping; Bao, Zhenan (Physical Chemistry Chemical Physics, 2015)

Role of acceptor strength on OFET properties of small molecular organic semiconducting materials with D-A-D architecture - Sasikumar, M.; Bharath, D.; Kumar, G. Siva; Chereddy, Narendra Reddy; Chithiravel, S.; Krishnamoorthy, K.; Shanigaram, Balaiah; Bhanuprakash, K.; Rao, V. Jayathirtha (Synthetic Metals, 2016)
Two organic semiconducting materials 2,5-didodecyl-3,6-bis(4-(11-dodecyl-11H-benzo[a]carbazol-8yl)phenyl)pyrrolo[3,4-c]pyrrole-1,4(2H,5H)-dione. (BCDPP) and 1,5-didodecyl-3,7-bis(4-(11-dodecyl-11H-benzo[a]carbazol-8-yl)phenyl)dipyrrolo[3,2-b:3',2'-e]pyrazine-2,6(1H,5H)-dione (BCPzDP) with D-A-D architecture have been designed, synthesized and well characterized. Both the materials have benzocarbazole donor end-capping units. While BCDPP contains well explored diketopyrrolopyrrole (DPP), BCPzDP possesses electron deficient dipyrrolopyrazinedione (PzDP) as acceptor moiety. The importance of the nature of acceptor moiety in tuning the charge transport properties of the synthesized materials is explored. Thermal, photo-physical and electrochemical properties of these materials are measured and solution processed OFETs are fabricated. OFETs with BCDPP show unipolar p-type semiconducting properties with hole mobility of 1.02 x 10(-4) cm(2) V-1 s(-1) and OFETs of BCPzDP exhibit ambipolar charge transport behaviour with optimal saturation hole and electron mobilities of 0.0054 and 0.0013 cm(2) V-1 s(-1), respectively. (C) 2016 Elsevier B.V. All rights reserved.

Facile synthesis of β-functionalized “push-pull” Zn(II) porphyrins for DSSC applications - Prakash, K. (Dyes and Pigments, 2017)
Three new β-substituted “push-pull” Zn(II) porphyrin dyes with various electron donors at meso-positions and cyanoacetic acid as acceptor at β-position have been designed and synthesized. These porphyrins have been characterized by UV-Vis, Fluorescence, 1H NMR and 13C NMR spectroscopic techniques and cyclic voltammetric studies. The Soret and Q band of Zn(II) porphyrin dyes were found to be red-shifted (30–35 nm) as compared to ZnTPP. The fluorescence quenching and the decrement in quantum yield and lifetime suggest intramolecular charge transfer from donor to acceptor. Zn porphyrins exhibited anodic shift in their first redox potentials (0.03–0.11 V) as compared to ZnTPP. The HOMO-LUMO energy levels of Zn porphyrin dyes were compared with the conduction band of TiO2 and the electrolyte I−/I3 −. The HOMO levels of all the dyes are sufficiently higher than the energy level of electrolyte I−/I3 − and LUMO levels significantly lower than the conduction band of TiO2 which reflect the feasibility of facile electron-transfer. ZnT(Mes)P(CN-COOH) has been co-sensitized with N719 dye to further improve the PCE efficiency. These dyes displayed power conversion efficiency (PCE) of η = 1.72–3.13% where co-sensitized ZnT(Mes)P(CN-COOH) (N719) dye demonstrated maximum PCE efficiency up to 5.35%, with a Jsc of 11.8 mA cm−2, a Voc of 630 mV and a fill factor (FF) of 72% due to better light harvesting capacity.
Keywords: charge transfer; Conduction Bands; Cyanoacetic Acid; Electrolytes; Floorescence; Redox Reaction; zinc compounds

Large anion incorporation to improve the performance of large, paper based conducting polymer supercapacitors - Jain, B.; Krishnamoorthy, K. (Materials Today Energy, 2017)
Poly(3,4-ethylenedioxythiophene) (PEDOT) is a stable conducting polymer, hence its dispersion is widely used in commercial devices. However, PEDOT's charge storage properties are not impressive. Thus, improvement in charge storage properties of PEDOT will render the possibility of fabricating stable energy storage devices such as supercapacitors. A fundamentally different approach is required to achieve this objective. We envisioned that the charge storage property of PEDOT can be improved by trapping large anions. These ions would facilitate better ion transport into the PEDOT matrix from the electrolyte and increase the efficiency of supercapacitors. Furthermore, a large anion such as triiodide is relatively immobile in the polymer matrix, hence we hypothesize the ions to be trapped in the polymer. To test this hypothesis, triiodide trapped PEDOT based supercapacitors are fabricated on paper substrates. A 1 cm2 triiodide incorporated PEDOT based supercapacitor exhibited a specific capacitance of 486 F/g. On the other hand, PEDOT without triiodide incorporation exhibited a specific capacitance of 221 F/g. Indeed, a device with an area of 32 cm2 exhibited a specific capacitance of 476 F/g.
Keywords: Flexible Supercapacitors; Paper based Supercapacitors; polyphenols

Organocatalytic Enantioselective Vinylogous Michael-Aldol Cascade for the Synthesis of Spirocyclic Compounds - Jain, B. (Electrochimica Acta, 2017)
Nanoscopic spheres of poly(3,4-ethylenedioxythiophene) from its poly(styrene sulfonate) stabilised dispersion was converted to nanofibers by acid treatment. The nanofibers showed a conductivity of 1800 S/cm. The specific capacitance of nanofiber based supercapcitors increased by 10 times compared to nanospeheres. The specific capacitance and power density were found to be 288 F/g and 9491 W/kg.

Improved efficiency of DSSC using combustion synthesized TiO2 - Umale, Sanjivani; Sudhakar, V.; Sontakke, Sharad M.; Krishnamoorthy, K.; Pandit, Aniruddha B. (Materials Research Bulletin, 2019)
Combustion synthesis method is an economic, one step and an effective method for the synthesis of nanomaterials. In this work, titanium dioxide nanoparticles were synthesized by combustion method. The synthesized material was characterized by XRD, SEM and BET. Dye sensitized solar cell was fabricated using the synthesized material and its performance was compared with the solar cell fabricated using commercial TiO2. In order to evaluate the photovoltaic performance of DSSCs, photocurrent density to photovoltage (J-V) characteristic and electrochemical impedance spectroscopy (EIS) measurements were carried out. The DSSC fabricated using combustion synthesized and commercial TiO2 exhibited a power conversion efficiency of 6.11% and 6.62%, respectively. Combustion synthesized TiO2 which displayed similar efficiency to that of commercial material is least studied in the literature for solar cell applications.
Keywords: Combustion synthesis; Dye sensitized solar cell; TiO2

Direct (hetero)arylation (DHAP) polymerization of conjugated polymers - new A-B-A monomer design for P(NDI2OD-T2) & the challenges of adopting DHAP for continuous flow processes - Kakde, Navnath R.; Bharathkumar, H. J.; Wavhal, Bhaiyyasaheb A.; Nikam, Arun; Patil, Suneha; Dash, Soumya Ranjan; Vanka, Kumar; Krishnamoorthy, K.; Kulkarni, Amol; Asha, S. K. (Journal of Materials Chemistry C, 2022)
P(NDI2OD-T2), also known as Polyera ActivInk N2200, was synthesized by the atom-economic direct hetero arylation polymerization (DHAP) route using a newly designed A-B-A monomer. The new monomer design involved flanking naphthalene diimide with bithiophene units in the bay position, which was further polymerized with bay substituted 1,4-dibromo naphthalene diimide, to afford the same polymer structure as P(NDI2OD-T2). The new monomer design resulted in a very high molecular weight (M-n: 99.5 kDa, D-M: 2.8) defect-free polymer in a quantitative yield by the DHAP batch process using 1,2,4-trichlorobenzene (TCB) as the solvent. DFT studies revealed that the abstraction of the alpha-proton from the naphthalene diimide substituted 2,2 `-bithiophene was favorable by 2.6 kcal mol(-1) (Delta Delta G) as compared to that from 2,2 `-bithiophene. The reason for this improved C-H activation at the alpha position can be attributed to the presence of C-HMIDLINE HORIZONTAL ELLIPSIS pi stabilizing interactions in naphthalene diimide substituted 2,2 `-bithiophene, which strengthens upon the extended charge delocalization throughout the ring, thus stabilizing the conjugate base generated after the proton abstraction. Continuous flow polymerization was carried out by pumping the DHAP reaction mixture including the monomers, catalyst, and additive (pivalic acid) solubilized in degassed TCB through a pre-heated glass condenser packed with K2CO3 and Celite under aerobic conditions. Reproducible molecular weights of M-n: 29.5 kDa, D-M: 1.7 were obtained at much lower concentrations of reactant mixture compared to that for batch polymerization. This is the first report of the synthesis of P(NDI2OD-T2) by a Continuous Flow Process adopting the DHAP route to obtain a defect-free polymer with reasonable molecular weights. P(NDI2OD-T2) was also synthesized by Stille polymerization as a reference control sample to compare the thermal and charge carrier transport properties of the DHAP polymers. Organic field-effect (OFET) mobility measurements indicated mobility values in the order of 10(-3) cm(2) V-1 s(-1) for the DHAP batch polymer (using the novel monomer design). The P(NDI2OD-T2) synthesized by DHAP batch using the commonly used starting materials - bisbromo naphthalene diimide and bithiophene, exhibited OFET mobilities which were one order less, similar to 10(-4) cm(2) V-1 s(-1). This observation highlights the importance of structural design in the monomer to enhance reactivity and thereby the bulk properties using the DHAP route.